Exploring the socio-ecological levels for prevention of sexual risk behaviours of the youth in uMgungundlovu District Municipality, KwaZulu-Natal - Nelisiwe Khuzwayo; Myra Taylor (AOSIS, 2018)
Background: Prevention of youth sexual risk behaviour among the youth in uMgungundlovu District Municipality continues to be a primary challenge for public health and health promotion. Current prevention interventions are targeted at an individual level, whilst youth behaviour is influenced by many social and environmental factors. Aim: The aim of the study was to explore the factors influencing sexual risk behaviours of the youth at different socio-ecological levels in uMgungundlovu District Municipality. Methods: An explorative and descriptive qualitative study design was used, using in-depth interviews and focus group discussions for data collection. A framework analysis was used to develop themes derived from the socio-ecological theory. Results: Four themes were identified that influence youth to engage in sexual risk behaviours: (1) individual factors, related to role modelling behaviour, gender and negative stereotypes towards females; (2) the microsystem in which youth function including the influence of family and peers; (3) the exo-system comprising the disadvantaged socio-economic status of the communities where the youth live; and (4) the macrosystem where negative social norms were reported to influence youth health outcomes. Conclusion: Sexual risk behaviour among youth in uMgungundlovu is influenced by many factors at multiple social levels. Interventions directed at these multiple levels are needed urgently.